Manufacturing process of fluorescent rubber cake
The synthetic and coated Mn4+ doped fluoride red phosphor is solved by wet chemistry, which solves the problems of poor moisture resistance and discomfort in particle size, and achieves the improvement of luminescence performance and the optimization of application performance. It is suitable for LED lighting and backlight display fields.
Patent Information
- Application Number
- CN202411500130.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-25
Smart Images

Figure CN119505864A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorescent composite materials, and in particular relates to a production process of fluorescent glue cakes. Background Art
[0002] With the continuous development of lighting and display technology, white light LED (WLED) has become the new generation of lighting source with the greatest development potential. In WLED, phosphor materials play a vital role, and their performance directly affects the optical performance and service life of WLED. 4+ Doped fluoride red phosphor (general formula: A2MF6:Mn 4+ ) has become an indispensable red light-emitting component in WLED due to its unique light-emitting properties.
[0003] Mn 4+ The doped fluoride red phosphor is a narrow-band emission phosphor that can emit strong red light in the 610-650nm wavelength range where the human eye is most sensitive. 4+ Fluoride-doped red phosphor has the following advantages:
[0004] High light efficiency: Mn 4+ Fluoride-doped red phosphor has high luminous efficiency in the red light band and can effectively improve the luminous efficiency of WL ED.
[0005] Wide color gamut: Due to its narrowband emission characteristics, Mn 4+ Doping fluoride red phosphor can broaden the color gamut of WLED, making its color rendering index higher and its color rendering performance better.
[0006] Excellent thermal stability: Compared with other red phosphors, Mn 4+ Fluoride-doped red phosphors have better thermal stability and less luminous intensity attenuation at high temperatures.
[0007] Mn 4+ Doped fluoride red phosphor can be compounded with other phosphors and applied in different fields. In the field of lighting, it can be compounded with yellow-green GaYAG or yellow YAG phosphors to prepare white light LED lamps with high color rendering index. In the field of display, it can be compounded with Sialon phosphors and applied to LED backlight sources to improve the color gamut of liquid crystal displays.
[0008] In lighting applications, Mn 4+ Fluoride-doped red phosphors are mainly used in filaments and patches. In order to improve their stability and brightness, it is usually necessary to increase the particle size of the phosphor. However, in backlight applications, due to the limitation of chip size, it is necessary to use Mn with a smaller particle size. 4+ Fluoride-doped red phosphor.
[0009] Although Mn 4+ Doped fluoride red phosphor has the above advantages, but there are still some problems to be solved in practical applications, mainly including:
[0010] Low moisture resistance: Mn 4+ Surface Mn of fluoride-doped red phosphor 4+ The ions are very easy to combine with water molecules and be oxidized, resulting in a significant decrease in the luminous intensity of the phosphor. This low moisture resistance seriously restricts its application in high humidity environments.
[0011] The contradiction between particle size and application field: In lighting applications, Mn with larger particle size is required. 4+ Fluoride red phosphors are doped to improve their stability and brightness; however, in backlight applications, due to chip size limitations, phosphors with smaller particle sizes need to be used. This contradiction between particle size and application areas poses a challenge to the preparation and application of materials.
[0012] Agglomeration of phosphors: During the preparation process, Mn 4+ Fluoride-doped red phosphors tend to agglomerate and form large particles, which not only affects the dispersibility of the phosphors but also leads to uneven luminescence.
[0013] The color purity of phosphor is not ideal: At present, Mn 4+ The color purity of fluoride-doped red phosphors needs to be further improved. Improving color purity can make WLEDs have a higher color rendering index and better color rendering performance.
[0014] In summary, Mn 4+ Although doped fluoride red phosphors have excellent luminescence properties, they still have problems such as poor moisture resistance, inconsistency between particle size and application field, serious agglomeration, and unsatisfactory color purity in practical applications. These problems seriously restrict the development of Mn 4+ The promotion and application of fluoride-doped red phosphors urgently requires researchers to propose new solutions.
[0015] In recent years, researchers have proposed some improvement measures to address the above problems. For example, improving the moisture resistance of phosphors by surface coating modification; optimizing the production process and regulating the particle size of phosphors; using core-shell structures to improve the luminescence properties of phosphors. Although these measures have improved the Mn 4+ The performance of fluoride-doped red phosphors is good, but it is still far from practical application. Therefore, the development of new Mn 4+ The preparation technology of fluoride-doped red phosphor and further improving its comprehensive performance are still urgent issues to be solved. Summary of the invention
[0016] 1. Problems to be solved
[0017] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a process for producing fluorescent glue cakes, which uses a wet chemical method to synthesize a precursor, and then undergoes coating and heat treatment to obtain a fluorescent glue cake with excellent luminescence performance and stable color. The production process of this method is relatively simple, the raw materials are easily available, and the cost is low. By optimizing the reaction conditions of each step, the large-scale preparation of fluorescent glue cakes can be achieved. Coating a dense Al2O3 film on the surface of the phosphor can significantly improve its moisture resistance. The coating layer can effectively block water molecules and prevent Mn 4+ Ion hydrolysis, thereby maintaining the stability of the luminescence performance of the phosphor. The coated phosphor is vitrified, and while further improving the moisture resistance, the particle size distribution of the phosphor can also be adjusted to obtain spherical particles with uniform particle size and good dispersibility, which is beneficial for application in devices such as LEDs. The fluorescent glue cake prepared by the present invention has high luminous efficiency and good color purity, and the emission peak is located at 600-630nm, making it an ideal red phosphor. Compared with other red phosphors, the quantum efficiency of this material under blue light excitation can reach more than 85%, which can significantly improve the color rendering index and luminous efficiency of white light LEDs. The fluorescent glue cake of the present invention can be widely used in LED lighting, backlight display and other fields, and has good application prospects. The white light LED light source prepared by the fluorescent powder has obvious advantages in high color rendering, high luminous efficiency, long life, etc., and can replace traditional fluorescent lamps and incandescent lamps, and has a broad market space. In summary, the fluorescent glue cake provided by the present invention solves the existing Mn 4+ The invention has obvious technical advantages and application value in solving the problem of unstable performance of fluoride-doped fluorescent gel cakes. The invention enriches the variety of red fluorescent powders for LEDs and has positive significance for promoting the development of semiconductor lighting and display technology.
[0018] 2. Technical solution
[0019] To solve the above problems, the technical solution provided by the present invention is:
[0020] A fluorescent glue cake, the chemical structure of which is shown in formula (I):
[0021] A l (B m , C n ):D o (I);
[0022] In formula (I), A is one of Na, Mg, and K, B is Si or Ce, C is F, and D is Mn 4+ , 1 <l<3,1<m<3,4<n<8,0.01<o<0.1。
[0023] Preferably, the chemical structure of the fluorescent glue cake is as shown in formula (II):
[0024] K2(Si,F6):Mn 4+ 0.06 (II).
[0025] The production process of the fluorescent glue cake comprises the following steps:
[0026] (a) precooling hydrofluoric acid with a concentration of 35wt%-45wt%, then adding potassium permanganate, stirring for the first time, then adding potassium fluoride, stirring for the second time, then adding hydrogen peroxide, adding hydrogen peroxide dropwise until the entire solution turns brown after the titration is completed, stopping the titration, then after the precipitate is completely left to stand and sink to the bottom, removing the upper layer of the solution, adding anhydrous ethanol to wash, washing until neutral, and drying after washing to obtain a first product;
[0027] (b) dissolving metasilicic acid in 35wt%-45wt% hydrofluoric acid and 10wt%-20wt% oxalic acid, stirring for the third time to obtain a second product;
[0028] (c) dissolving potassium fluoride hydrogen in hydrofluoric acid having a concentration of 35 wt % to 45 wt %, and stirring for a fourth time to obtain a third product;
[0029] (d) mixing hydrofluoric acid with the first product, stirring for the fifth time, then adding the second product and the third product 5-8 seconds after the start of the fifth stirring, stirring for the sixth time, standing for 2 minutes to 10 minutes after the stirring stops, and after the precipitate settles to the bottom, pouring off the supernatant, washing the precipitate with anhydrous ethanol until it is neutral, and drying the washed product;
[0030] (e) subjecting the dried product of step (d) to an atomic layer deposition process to obtain a coated product, and then mixing the coated product with glass powder, subjecting the mixture to a high temperature treatment, and cooling the mixture naturally.
[0031] Preferably, the temperature of the low-temperature precooling in step (a) of the fluorescent glue cake production process is 0°C-4°C;
[0032] The low temperature precooling method in step (a) is an ice bath;
[0033] In step (a), the mass of potassium permanganate added is 10 to 15 times that of hydrofluoric acid;
[0034] The first stirring time in step (a) is 5 min-20 min, and the first stirring speed is 300 rpm-500 rpm;
[0035] The mass of potassium fluoride added in step (a) is 150 to 250 times that of hydrofluoric acid;
[0036] The second stirring time in step (a) is 20 min-40 min, and the second stirring speed is 200 rpm-400 rpm;
[0037] In step (a), the mass concentration of hydrogen peroxide is 30%, the mass of hydrogen peroxide added is 10 to 20 times that of hydrofluoric acid, the dropping speed of hydrogen peroxide is 1 drop / s, and the dropping method of hydrogen peroxide is dropwise addition using a separatory funnel;
[0038] The drying temperature in step (a) is 60°C-80°C.
[0039] Preferably, in the step (b) of the production process of the fluorescent glue cake, the mass ratio of metasilicic acid, hydrofluoric acid and oxalic acid is (15-25): (100-120): (80-90);
[0040] The third stirring time in step (b) is 30 min-40 min, and the second stirring speed is 250 rpm-400 rpm;
[0041] In step (c), the mass ratio between potassium fluoride hydrogen and hydrofluoric acid is (45-65): (160-200);
[0042] The fourth stirring time in step (d) is 25 min-50 min, and the second stirring speed is 250 rpm-300 rpm.
[0043] Preferably, in the step (d) of the production process of the fluorescent glue cake, the mass ratio between the hydrofluoric acid and the first product is (400-600): (5-15);
[0044] The fifth stirring time in step (d) is 30 min-50 min, and the second stirring speed is 400 rpm-600 rpm;
[0045] In step (d), the mass ratio of hydrofluoric acid to the second product and the third product is (1-3): (2-5): (3-5);
[0046] The sixth stirring time in step (d) is 10 min-30 min, and the second stirring speed is 400 rpm-600 rpm;
[0047] The drying temperature in step (d) is 70°C-90°C.
[0048] Preferably, the method of atomic layer deposition in step (e) of the manufacturing process of the fluorescent glue cake is as follows:
[0049] The dried product is placed in an atomic layer deposition reaction chamber, and the vacuum is evacuated to 10Pa under a nitrogen atmosphere. The reaction chamber is heated to a reaction temperature of 50°C-90°C, and trimethylaluminum vapor is introduced as an aluminum source precursor for a time of 0.1s-10s. The introduction is stopped, and the reaction chamber is purged with nitrogen for a time of 1s-60s. Then, ozone gas is introduced into the reaction chamber for a time of 0.1s-10s, and the reaction chamber is purged with nitrogen again until a 1nm film layer is deposited. The film is cooled to room temperature under a nitrogen atmosphere to obtain a coated product;
[0050] The manufacturing process of the glass powder in step (e) is as follows:
[0051] Mix B2O3, SiO2, ZnO and Na2O in a mass ratio of 10:60:20:10, calcine at 1000-1200℃ for 2h-4h, cool to room temperature, ball mill and pass through a 200-mesh sieve to obtain;
[0052] In step (e), the mass ratio between the coated product and the glass powder is 1:(6-10);
[0053] The temperature of the high temperature treatment in step (e) is 700° C.-800° C., and the time of the high temperature treatment is 10 min-30 min.
[0054] 3. Beneficial effects
[0055] In the application of phosphors, particle size is a key parameter, which directly affects the optical properties and application effects of phosphors. In the field of lighting and display, different application scenarios have different requirements for the particle size of phosphors. For example, in the field of lighting, larger particle size helps to improve the stability and brightness of phosphors, while in backlight applications, due to the limitation of chip size, phosphors with smaller particle size need to be used. By optimizing the production process, the technology of this application can accurately control the particle size of fluoride phosphors to meet the needs of different markets. Specifically, by adjusting the amount of HF and the stirring speed in the KHF2 solution, products with different particle sizes can be prepared. For example, increasing the amount of HF can obtain a product with a large particle size, while increasing the stirring speed can obtain a product with a small particle size. This flexible particle size control capability enables our products to be widely used in various lighting and display scenarios. Mn 4+ The doped fluoride red phosphor has a surface Mn 4+ Ions are easily oxidized after combining with water, resulting in a decrease in luminescence intensity. Therefore, its low moisture resistance has always been an important factor restricting its application. By coating a dense, high-temperature resistant inorganic film on the surface of the phosphor, water molecules can be effectively prevented from oxidizing and reacting with Mn. 4+ion contact, thereby significantly improving the moisture resistance of the powder. The thickness of this inorganic film is controllable, and the coating thickness can be adjusted by setting the number of cycles, thereby indirectly regulating the particle size of the powder. In addition, this surface coating treatment not only improves the moisture resistance, but also significantly improves the thermal stability and chemical stability of the powder. In traditional inorganic coating treatment, vitrification treatment is a commonly used method, but it needs to be carried out under high temperature conditions, which may have an adverse effect on the powder. The technology of the present application can reduce the impact of high temperature on the powder by vitrification treatment after coating a layer of high-temperature resistant inorganic film on the surface. This optimized vitrification treatment process makes the coating layer more uniform and dense, and has a better protection effect on the surface. Specifically, the vitrification treatment uses a mixture of B2O3-SiO2-ZnO-Na2O, which is calcined at high temperature to form a uniform glass layer. This treatment not only improves the moisture resistance and thermal stability of the powder, but also enhances its mechanical strength, making the phosphor more durable in practical applications. The production process of the present application is simple and efficient, and is suitable for large-scale industrial production. By optimizing each production step, we can improve production efficiency and reduce production costs while ensuring product quality. This efficient production process makes our products more competitive in the market. In summary, the technology of this application has significant advantages over the commonly used technologies in the current market in terms of particle size control, moisture resistance improvement, vitrification treatment and production efficiency. These advantages enable our products to better meet market demand and stand out in the fierce market competition. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 is a scanning electron microscope image of the fluorescent glue cake of Example 5 of the present invention;
[0057] Figure 2 This is a particle size diagram of the fluorescent glue cake of Example 5 of the present invention. DETAILED DESCRIPTION
[0058] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] It should be noted that, in the present invention, all weight parts involved are international standard units kilograms (Kg).
[0060] Example 1
[0061] Fluorescent glue cake, the chemical structure of the fluorescent glue cake is shown in formula (III): A2 (B2, C5): D 0.02(III);
[0062] In formula (III), A is Na, B is Ce, C is F, and D is Mn 4+ .
[0063] The production process of the fluorescent glue cake comprises the following steps: (a) precooling 35wt% hydrofluoric acid at low temperature, then adding potassium permanganate, stirring for the first time, then adding potassium fluoride, stirring for the second time, then adding hydrogen peroxide, adding hydrogen peroxide dropwise until the whole solution turns brown after the titration is completed, stopping the titration, and then removing the upper layer solution after the precipitate is completely left to settle to the bottom, adding anhydrous ethanol for washing, washing until neutral, and drying after washing to obtain the first product;
[0064] It should be noted that the temperature of low temperature precooling in step (a) is 0°C;
[0065] The low temperature precooling method in step (a) is an ice bath;
[0066] The mass of potassium permanganate added in step (a) is 10 times that of hydrofluoric acid;
[0067] The first stirring time in step (a) is 5 min, and the first stirring speed is 500 rpm;
[0068] The mass of potassium fluoride added in step (a) is 150 times that of hydrofluoric acid;
[0069] The second stirring time in step (a) is 20 min, and the second stirring speed is 400 rpm;
[0070] In step (a), the mass concentration of hydrogen peroxide is 30%, the added mass of hydrogen peroxide is 10 times that of hydrofluoric acid, the dropping speed of hydrogen peroxide is 1 drop / s, and the dropping method of hydrogen peroxide is dropwise addition using a separatory funnel;
[0071] The drying temperature in step (a) is 60°C.
[0072] (b) dissolving metasilicic acid in 35 wt % hydrofluoric acid and 20 wt % oxalic acid, stirring for the third time to obtain a second product;
[0073] It should be noted that the mass ratio of metasilicic acid, hydrofluoric acid and oxalic acid in step (b) is 15:120:80;
[0074] The third stirring time in step (b) is 30 min, and the second stirring speed is 400 rpm.
[0075] (c) dissolving potassium fluoride hydrogen in 35 wt % hydrofluoric acid and stirring for a fourth time to obtain a third product;
[0076] It should be noted that the mass ratio between potassium fluoride and hydrofluoric acid in step (c) is 45:200.
[0077] (d) mixing hydrofluoric acid with the first product, stirring for the fifth time, then adding the second product and the third product 5 seconds after the start of the fifth stirring, stirring for the sixth time, standing for 10 minutes after the stirring stops, and after the precipitate settles to the bottom, pouring off the supernatant, washing the precipitate with anhydrous ethanol until it is neutral, and drying the washed product;
[0078] It should be noted that the fourth stirring time in step (d) is 25 min, and the second stirring speed is 300 rpm.
[0079] It should be noted that the mass ratio between hydrofluoric acid and the first product in step (d) is 400:15;
[0080] The fifth stirring time in step (d) is 30 min, and the second stirring speed is 600 rpm;
[0081] In step (d), the mass ratio of hydrofluoric acid to the second product and the third product is 1:5:3;
[0082] The sixth stirring time in step (d) is 10 min, and the second stirring speed is 600 rpm;
[0083] The drying temperature in step (d) is 70°C.
[0084] (e) subjecting the product obtained after drying in step (d) to an atomic layer deposition process to obtain a coated product, and then mixing the coated product with glass powder, subjecting the mixture to a high temperature treatment, and cooling the mixture naturally;
[0085] The method of atomic layer deposition treatment in step (e) is as follows: placing the dried product in an atomic layer deposition reaction chamber, evacuating to 10 Pa under a nitrogen atmosphere, heating the reaction chamber to a reaction temperature of 50° C., introducing trimethylaluminum vapor as an aluminum source precursor for 10 seconds, stopping the introduction, purging the reaction chamber with nitrogen for 1 second, then introducing ozone gas into the reaction chamber for 10 seconds, purging the reaction chamber with nitrogen again until a 1 nm film layer is deposited, cooling to room temperature under a nitrogen atmosphere, and obtaining a coated product;
[0086] The preparation process of the glass powder in step (e) is as follows: B2O3, SiO2, ZnO and Na2O are mixed in a mass ratio of 10:60:20:10, calcined at 1000°C for 4 hours, cooled to room temperature, ball-milled and sieved through a 200-mesh sieve to obtain the glass powder;
[0087] In step (e), the mass ratio between the coated product and the glass powder is 1:6;
[0088] The temperature of the high temperature treatment in step (e) is 700° C., and the time of the high temperature treatment is 30 minutes.
[0089] Example 2
[0090] Fluorescent glue cake, the chemical structure of the fluorescent glue cake is shown in formula (V): A2 (B2, C5): D 0.09 (V);
[0091] In formula (V), A is Mg, B is Si, C is F, and D is Mn 4+ .
[0092] The production process of the fluorescent glue cake comprises the following steps: (a) precooling 45wt% hydrofluoric acid at low temperature, then adding potassium permanganate, stirring for the first time, then adding potassium fluoride, stirring for the second time, then adding hydrogen peroxide, adding hydrogen peroxide dropwise until the whole solution turns brown after the titration is completed, stopping the titration, and then removing the upper layer solution after the precipitate is completely left to settle to the bottom, adding anhydrous ethanol for washing, washing until neutral, and drying after washing to obtain the first product;
[0093] It should be noted that the temperature of low temperature precooling in step (a) is 4°C;
[0094] The low temperature precooling method in step (a) is an ice bath;
[0095] The mass of potassium permanganate added in step (a) is 15 times that of hydrofluoric acid;
[0096] The first stirring time in step (a) is 20 min, and the first stirring speed is 300 rpm;
[0097] The mass of potassium fluoride added in step (a) is 250 times that of hydrofluoric acid;
[0098] The second stirring time in step (a) is 40 min, and the second stirring speed is 200 rpm;
[0099] In step (a), the mass concentration of hydrogen peroxide is 30%, the added mass of hydrogen peroxide is 20 times that of hydrofluoric acid, the dropping speed of hydrogen peroxide is 1 drop / s, and the dropping method of hydrogen peroxide is dropwise addition using a separatory funnel;
[0100] The drying temperature in step (a) is 80°C.
[0101] (b) dissolving metasilicic acid in 45 wt % hydrofluoric acid and 10 wt % oxalic acid, stirring for the third time to obtain a second product;
[0102] It should be noted that the mass ratio of metasilicic acid, hydrofluoric acid and oxalic acid in step (b) is 25:100:90;
[0103] The third stirring time in step (b) is 40 min, and the second stirring speed is 250 rpm.
[0104] (c) dissolving potassium fluoride hydrogen in 45 wt % hydrofluoric acid and stirring for the fourth time to obtain a third product;
[0105] It should be noted that the mass ratio between potassium fluoride and hydrofluoric acid in step (c) is 65:160.
[0106] (d) mixing hydrofluoric acid with the first product, stirring for the fifth time, then adding the second product and the third product 8 seconds after the start of the fifth stirring, stirring for the sixth time, standing for 2 minutes after the stirring stops, and after the precipitate settles to the bottom, pouring off the supernatant, washing the precipitate with anhydrous ethanol until it is neutral, and drying the washed product;
[0107] It should be noted that the fourth stirring time in step (d) is 50 min, and the second stirring speed is 250 rpm.
[0108] It should be noted that the mass ratio between hydrofluoric acid and the first product in step (d) is 600:5;
[0109] The fifth stirring time in step (d) is 50 min, and the second stirring speed is 400 rpm;
[0110] In step (d), the mass ratio of hydrofluoric acid to the second product and the third product is 3:2:5;
[0111] The sixth stirring time in step (d) is 30 min, and the second stirring speed is 400 rpm;
[0112] The drying temperature in step (d) is 90°C.
[0113] (e) subjecting the product obtained after drying in step (d) to an atomic layer deposition process to obtain a coated product, and then mixing the coated product with glass powder, subjecting the mixture to a high temperature treatment, and cooling the mixture naturally;
[0114] The method of atomic layer deposition treatment in step (e) is as follows: placing the dried product in an atomic layer deposition reaction chamber, evacuating to 10 Pa under a nitrogen atmosphere, heating the reaction chamber to a reaction temperature of 90° C., introducing trimethylaluminum vapor as an aluminum source precursor for 0.1 s, stopping the introduction, purging the reaction chamber with nitrogen for 60 s, then introducing ozone gas into the reaction chamber for 0.1 s, purging the reaction chamber with nitrogen again until a 1 nm film layer is deposited, cooling to room temperature under a nitrogen atmosphere, and obtaining a coated product;
[0115] The preparation process of the glass powder in step (e) is as follows: B2O3, SiO2, ZnO and Na2O are mixed in a mass ratio of 10:60:20:10, calcined at 1200°C for 2h, cooled to room temperature, ball-milled and sieved through a 200-mesh sieve to obtain the glass powder;
[0116] In step (e), the mass ratio between the coated product and the glass powder is 1:10;
[0117] The temperature of the high temperature treatment in step (e) is 800° C., and the time of the high temperature treatment is 10 minutes.
[0118] Example 3
[0119] Fluorescent glue cake, the chemical structure of the fluorescent glue cake is shown in formula (VI): A2(B2, C7):D 0.03 (VI);
[0120] In formula (VI), A is K, B is Ce, C is F, and D is Mn 4+ .
[0121] The production process of the fluorescent glue cake comprises the following steps: (a) precooling 35wt% hydrofluoric acid at low temperature, then adding potassium permanganate, stirring for the first time, then adding potassium fluoride, stirring for the second time, then adding hydrogen peroxide, adding hydrogen peroxide dropwise until the whole solution turns brown after the titration is completed, stopping the titration, and then removing the upper layer solution after the precipitate is completely left to settle to the bottom, adding anhydrous ethanol for washing, washing until neutral, and drying after washing to obtain the first product;
[0122] It should be noted that the temperature of low temperature precooling in step (a) is 0°C;
[0123] The low temperature precooling method in step (a) is an ice bath;
[0124] The mass of potassium permanganate added in step (a) is 10 times that of hydrofluoric acid;
[0125] The first stirring time in step (a) is 5 min, and the first stirring speed is 300 rpm;
[0126] The mass of potassium fluoride added in step (a) is 150 times that of hydrofluoric acid;
[0127] The second stirring time in step (a) is 20 min, and the second stirring speed is 200 rpm;
[0128] In step (a), the mass concentration of hydrogen peroxide is 30%, the added mass of hydrogen peroxide is 10 times that of hydrofluoric acid, the dropping speed of hydrogen peroxide is 1 drop / s, and the dropping method of hydrogen peroxide is dropwise addition using a separatory funnel;
[0129] The drying temperature in step (a) is 60°C.
[0130] (b) dissolving metasilicic acid in 35 wt % hydrofluoric acid and 10 wt % oxalic acid, stirring for the third time to obtain a second product;
[0131] It should be noted that the mass ratio of metasilicic acid, hydrofluoric acid and oxalic acid in step (b) is 15:100:80;
[0132] The third stirring time in step (b) is 30 min, and the second stirring speed is 250 rpm.
[0133] (c) dissolving potassium fluoride hydrogen in hydrofluoric acid having a concentration of 35 wt % to 45 wt %, and stirring for a fourth time to obtain a third product;
[0134] It should be noted that the mass ratio between potassium fluoride hydrogen and hydrofluoric acid in step (c) is 45:160.
[0135] (d) mixing hydrofluoric acid with the first product, stirring for the fifth time, then adding the second product and the third product 5 seconds after the start of the fifth stirring, stirring for the sixth time, standing for 2 minutes after the stirring stops, and after the precipitate settles to the bottom, pouring off the supernatant, washing the precipitate with anhydrous ethanol until it is neutral, and drying the washed product;
[0136] It should be noted that the fourth stirring time in step (d) is 25 min, and the second stirring speed is 250 rpm.
[0137] It should be noted that the mass ratio between hydrofluoric acid and the first product in step (d) is 400:5;
[0138] The fifth stirring time in step (d) is 30 min, and the second stirring speed is 400 rpm;
[0139] In step (d), the mass ratio of hydrofluoric acid to the second product and the third product is 1:2:3;
[0140] The sixth stirring time in step (d) is 10 min, and the second stirring speed is 400 rpm;
[0141] The drying temperature in step (d) is 70°C.
[0142] (e) subjecting the product obtained after drying in step (d) to an atomic layer deposition process to obtain a coated product, and then mixing the coated product with glass powder, subjecting the mixture to a high temperature treatment, and cooling the mixture naturally;
[0143] The method of atomic layer deposition treatment in step (e) is as follows: placing the dried product in an atomic layer deposition reaction chamber, evacuating to 10 Pa under a nitrogen atmosphere, heating the reaction chamber to a reaction temperature of 50° C., introducing trimethylaluminum vapor as an aluminum source precursor for 0.1 s, stopping the introduction, purging the reaction chamber with nitrogen for 1 s, then introducing ozone gas into the reaction chamber for 0.1 s, purging the reaction chamber with nitrogen again until a 1 nm film layer is deposited, cooling to room temperature under a nitrogen atmosphere, and obtaining a coated product;
[0144] The preparation process of the glass powder in step (e) is as follows: B2O3, SiO2, ZnO and Na2O are mixed in a mass ratio of 10:60:20:10, calcined at 1000°C for 2h, cooled to room temperature, ball-milled and sieved through a 200-mesh sieve to obtain the glass powder;
[0145] In step (e), the mass ratio between the coated product and the glass powder is 1:6;
[0146] The temperature of the high temperature treatment in step (e) is 700° C., and the time of the high temperature treatment is 10 minutes.
[0147] Example 4
[0148] Fluorescent glue cake, the chemical structure of the fluorescent glue cake is shown in formula (VII): A2(B2, C6):D 0.07 (VII);
[0149] In formula (VII), A is K, B is Si, C is F, and D is Mn 4+ .
[0150] The production process of the fluorescent glue cake comprises the following steps: (a) precooling 45wt% hydrofluoric acid at low temperature, then adding potassium permanganate, stirring for the first time, then adding potassium fluoride, stirring for the second time, then adding hydrogen peroxide, adding hydrogen peroxide dropwise until the whole solution turns brown after the titration is completed, stopping the titration, and then removing the upper layer solution after the precipitate is completely left to settle to the bottom, adding anhydrous ethanol for washing, washing until neutral, and drying after washing to obtain the first product;
[0151] It should be noted that the temperature of low temperature precooling in step (a) is 4°C;
[0152] The low temperature precooling method in step (a) is an ice bath;
[0153] The mass of potassium permanganate added in step (a) is 15 times that of hydrofluoric acid;
[0154] The first stirring time in step (a) is 20 min, and the first stirring speed is 500 rpm;
[0155] The mass of potassium fluoride added in step (a) is 250 times that of hydrofluoric acid;
[0156] The second stirring time in step (a) is 40 min, and the second stirring speed is 400 rpm;
[0157] In step (a), the mass concentration of hydrogen peroxide is 30%, the added mass of hydrogen peroxide is 20 times that of hydrofluoric acid, the dropping speed of hydrogen peroxide is 1 drop / s, and the dropping method of hydrogen peroxide is dropwise addition using a separatory funnel;
[0158] The drying temperature in step (a) is 80°C.
[0159] (b) dissolving metasilicic acid in 45 wt % hydrofluoric acid and 20 wt % oxalic acid, stirring for the third time to obtain a second product;
[0160] It should be noted that the mass ratio of metasilicic acid, hydrofluoric acid and oxalic acid in step (b) is 25:120:90;
[0161] The third stirring time in step (b) is 40 min, and the second stirring speed is 400 rpm.
[0162] (c) dissolving potassium fluoride hydrogen in 45 wt % hydrofluoric acid and stirring for the fourth time to obtain a third product;
[0163] It should be noted that the mass ratio between potassium fluoride and hydrofluoric acid in step (c) is 65:200.
[0164] (d) mixing hydrofluoric acid with the first product, stirring for the fifth time, then adding the second product and the third product 8 seconds after the start of the fifth stirring, stirring for the sixth time, standing for 10 minutes after the stirring stops, and after the precipitate settles to the bottom, pouring off the supernatant, washing the precipitate with anhydrous ethanol until it is neutral, and drying the washed product;
[0165] It should be noted that the fourth stirring time in step (d) is 50 min, and the second stirring speed is 300 rpm.
[0166] It should be noted that the mass ratio between hydrofluoric acid and the first product in step (d) is 600:15;
[0167] The fifth stirring time in step (d) is 50 min, and the second stirring speed is 600 rpm;
[0168] In step (d), the mass ratio of hydrofluoric acid to the second product and the third product is 3:5:5;
[0169] The sixth stirring time in step (d) is 30 min, and the second stirring speed is 600 rpm;
[0170] The drying temperature in step (d) is 90°C.
[0171] (e) subjecting the product dried in step (d) to an atomic layer deposition process to obtain a coated product, and then mixing the coated product with glass powder, subjecting the mixture to a high temperature treatment, and cooling the mixture naturally;
[0172] The method of atomic layer deposition treatment in step (e) is as follows: placing the dried product in an atomic layer deposition reaction chamber, evacuating to 10 Pa under a nitrogen atmosphere, heating the reaction chamber to a reaction temperature of 90° C., introducing trimethylaluminum vapor as an aluminum source precursor for 10 seconds, stopping the introduction, purging the reaction chamber with nitrogen for 60 seconds, then introducing ozone gas into the reaction chamber for 10 seconds, purging the reaction chamber with nitrogen again until a 1 nm film layer is deposited, cooling to room temperature under a nitrogen atmosphere, and obtaining a coated product;
[0173] The preparation process of the glass powder in step (e) is as follows: B2O3, SiO2, ZnO and Na2O are mixed in a mass ratio of 10:60:20:10, calcined at 1200°C for 4 hours, cooled to room temperature, ball-milled and sieved through a 200-mesh sieve to obtain the glass powder;
[0174] In step (e), the mass ratio between the coated product and the glass powder is 1:10;
[0175] The temperature of the high temperature treatment in step (e) is 800° C., and the time of the high temperature treatment is 30 minutes.
[0176] Example 5
[0177] Fluorescent glue cake, the chemical structure of the fluorescent glue cake is shown in formula (II): K2(Si, F6):Mn 4+ 0.06 (II).
[0178] The production process of the fluorescent glue cake comprises the following steps: (a) precooling 40 wt% hydrofluoric acid at low temperature, then adding potassium permanganate, stirring for the first time, then adding potassium fluoride, stirring for the second time, then adding hydrogen peroxide, adding hydrogen peroxide dropwise until the whole solution turns brown after the titration is completed, stopping the titration, and then removing the upper layer solution after the precipitate is completely left to settle to the bottom, adding anhydrous ethanol for washing, washing until neutral, and drying after washing to obtain the first product;
[0179] It should be noted that the temperature of low temperature precooling in step (a) is 4°C;
[0180] The low temperature precooling method in step (a) is an ice bath;
[0181] The mass of potassium permanganate added in step (a) is 13 times that of hydrofluoric acid;
[0182] The first stirring time in step (a) is 10 min, and the first stirring speed is 400 rpm;
[0183] The mass of potassium fluoride added in step (a) is 150 to 250 times that of hydrofluoric acid;
[0184] The second stirring time in step (a) is 30 min, and the second stirring speed is 300 rpm;
[0185] In step (a), the mass concentration of hydrogen peroxide is 30%, the added mass of hydrogen peroxide is 15 times that of hydrofluoric acid, the dropping speed of hydrogen peroxide is 1 drop / s, and the dropping method of hydrogen peroxide is dropwise addition using a separatory funnel;
[0186] The drying temperature in step (a) is 70°C.
[0187] (b) dissolving metasilicic acid in 40 wt % hydrofluoric acid and 15 wt % oxalic acid, stirring for the third time to obtain a second product;
[0188] It should be noted that the mass ratio of metasilicic acid, hydrofluoric acid and oxalic acid in step (b) is 20:110:85;
[0189] The third stirring time in step (b) is 35 min, and the second stirring speed is 300 rpm.
[0190] (c) dissolving potassium fluoride hydrogen in 40 wt % hydrofluoric acid and stirring for the fourth time to obtain a third product;
[0191] It should be noted that the mass ratio between potassium fluoride hydrogen and hydrofluoric acid in step (c) is 55:180.
[0192] (d) mixing hydrofluoric acid with the first product, stirring for the fifth time, then adding the second product and the third product 7 seconds after the start of the fifth stirring, stirring for the sixth time, standing for 7 minutes after the stirring stops, and after the precipitate settles to the bottom, pouring off the supernatant, washing the precipitate with anhydrous ethanol until it is neutral, and drying the washed product;
[0193] It should be noted that the fourth stirring time in step (d) is 40 min, and the second stirring speed is 280 rpm.
[0194] It should be noted that the mass ratio between hydrofluoric acid and the first product in step (d) is 500:10;
[0195] The fifth stirring time in step (d) is 30 min-50 min, and the second stirring speed is 400 rpm-600 rpm;
[0196] In step (d), the mass ratio of hydrofluoric acid to the second product and the third product is 2:4:4;
[0197] The sixth stirring time in step (d) is 20 min, and the second stirring speed is 500 rpm;
[0198] The drying temperature in step (d) is 80°C.
[0199] (e) subjecting the product obtained after drying in step (d) to an atomic layer deposition process to obtain a coated product, and then mixing the coated product with glass powder, subjecting the mixture to a high temperature treatment, and cooling the mixture naturally;
[0200] The method of atomic layer deposition treatment in step (e) is as follows: placing the dried product in an atomic layer deposition reaction chamber, evacuating to 10 Pa under a nitrogen atmosphere, heating the reaction chamber to a reaction temperature of 80°C, introducing trimethylaluminum vapor as an aluminum source precursor for 5 seconds, stopping the introduction, purging the reaction chamber with nitrogen for 40 seconds, then introducing ozone gas into the reaction chamber for 6 seconds, purging the reaction chamber with nitrogen again until a 1 nm film layer is deposited, cooling to room temperature under a nitrogen atmosphere, and obtaining a coated product;
[0201] The preparation process of the glass powder in step (e) is as follows: B2O3, SiO2, ZnO and Na2O are mixed in a mass ratio of 10:60:20:10, calcined at 1100°C for 3h, cooled to room temperature, ball-milled and sieved through a 200-mesh sieve to obtain the glass powder;
[0202] In step (e), the mass ratio between the coated product and the glass powder is 1:8;
[0203] The temperature of the high temperature treatment in step (e) is 750° C., and the time of the high temperature treatment is 20 minutes.
[0204] Test plan
[0205] Referring to the test method of the prior art, patent authorization announcement number: CN104893718B (color-stable manganese-doped phosphor), high temperature and high humidity tests were carried out, and HTHH treatment was carried out in accordance with the standard (IEC60068-2-78), with a temperature of 85°C, a relative humidity of 85%, and a duration of 1000h. A 615nm excitation light source was used to test the luminous intensity of the samples before and after HTHH treatment, and finally the quantum efficiency (QE) of the samples was calculated.
[0206] Table 1 Test results
[0207] QE before treatment, % QE after treatment, % Example 1 100 90.2 Example 2 100 85.6 Example 3 100 93.5 Example 4 100 97.8 Example 5 100 98.4
[0208] As shown in Table 1, the results show that under high temperature and high humidity conditions, the quantum efficiency (QE) of different solutions decreased after treatment, but the decrease was different. Specifically:
[0209] Example 1: QE dropped from 100% to 90.2% before and after treatment.
[0210] Example 2: QE dropped from 100% to 85.6% before and after treatment.
[0211] Example 3: QE dropped from 100% to 93.5% before and after treatment.
[0212] Example 4: QE decreased from 100% to 97.8% before and after treatment.
[0213] Example 5: QE dropped from 100% to 98.4% before and after treatment.
[0214] These results show that Example 5 shows the smallest decrease in quantum efficiency under high temperature and high humidity conditions, showing good stability and durability. In contrast, Example 2 has the largest decrease in quantum efficiency, and may need to further optimize its chemical structure or improve its processing to improve its performance under harsh environments. Through these tests, important data support can be provided for subsequent material improvements and applications. In addition, for the fluorescent gel cake prepared in Example 5, its scanning electron microscope structure is shown in the figure below: Figure 1 Its particle size distribution is shown in Figure 2 As shown, the obtained fluorescent glue cake has good crystal quality and a relatively smooth surface. This smooth surface helps to improve its luminescence performance. The average particle size of the fluorescent glue cake particles is 4.82um, and the particle size of most powder particles is concentrated between 3.6 and 6.5um, showing relative uniformity of particle size distribution.
[0215] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A process for making a fluorescent glue cake, comprising the following steps: (a) precooling hydrofluoric acid with a concentration of 35wt%-45wt%, then adding potassium permanganate, stirring for the first time, then adding potassium fluoride, stirring for the second time, then adding hydrogen peroxide, adding hydrogen peroxide dropwise until the entire solution turns brown after the titration is completed, stopping the titration, then after the precipitate is completely left to stand and sink to the bottom, removing the upper layer of the solution, adding anhydrous ethanol to wash, washing until neutral, and drying after washing to obtain a first product; (b) dissolving metasilicic acid in 35wt%-45wt% hydrofluoric acid and 10wt%-20wt% oxalic acid, stirring for the third time to obtain a second product; (c) dissolving potassium fluoride hydrogen in hydrofluoric acid having a concentration of 35 wt % to 45 wt %, and stirring for a fourth time to obtain a third product; (d) mixing hydrofluoric acid with the first product, stirring for the fifth time, then adding the second product and the third product 5-8 seconds after the start of the fifth stirring, stirring for the sixth time, standing for 2 minutes to 10 minutes after the stirring stops, and after the precipitate settles to the bottom, pouring off the supernatant, washing the precipitate with anhydrous ethanol until it is neutral, and drying the washed product; (e) subjecting the dried product of step (d) to an atomic layer deposition process to obtain a coated product, and then mixing the coated product with glass powder, subjecting the mixture to a high temperature treatment, and cooling the mixture naturally.
2. The process for making the fluorescent glue cake according to claim 1, characterized in that: The temperature of low temperature precooling in step (a) is 0°C-4°C; The low temperature precooling method in step (a) is an ice bath; In step (a), the mass of potassium permanganate added is 10 to 15 times that of hydrofluoric acid.
3. The process for making the fluorescent glue cake according to claim 1, characterized in that: The first stirring time in step (a) is 5 min-20 min, and the first stirring speed is 300 rpm-500 rpm; The mass of potassium fluoride added in step (a) is 150 to 250 times that of hydrofluoric acid.
4. The process for making the fluorescent glue cake according to claim 1, characterized in that: The second stirring time in step (a) is 20 min-40 min, and the second stirring speed is 200 rpm-400 rpm; In step (a), the mass concentration of hydrogen peroxide is 30%, the mass of hydrogen peroxide added is 10 to 20 times that of hydrofluoric acid, the dropping speed of hydrogen peroxide is 1 drop / s, and the dropping method of hydrogen peroxide is dropwise addition using a separatory funnel; The drying temperature in step (a) is 60°C-80°C.
5. The process for making the fluorescent glue cake according to claim 1, characterized in that: In step (b), the mass ratio of metasilicic acid, hydrofluoric acid and oxalic acid is (15-25): (100-120): (80-90); The third stirring time in step (b) is 30 min-40 min, and the second stirring speed is 250 rpm-400 rpm.
6. The process for making the fluorescent glue cake according to claim 1, characterized in that: In step (c), the mass ratio between potassium fluoride hydrogen and hydrofluoric acid is (45-65): (160-200); The fourth stirring time in step (d) is 25 min-50 min, and the second stirring speed is 250 rpm-300 rpm.
7. The process for making the fluorescent glue cake according to claim 1, characterized in that: In step (d), the mass ratio between hydrofluoric acid and the first product is (400-600):(5-15); The fifth stirring time in step (d) is 30 min-50 min, and the second stirring speed is 400 rpm-600 rpm.
8. The process for making the fluorescent glue cake according to claim 1, characterized in that: In step (d), the mass ratio of hydrofluoric acid to the second product and the third product is (1-3): (2-5): (3-5); The sixth stirring time in step (d) is 10 min to 30 min, and the second stirring speed is 400 rpm to 600 rpm; The drying temperature in step (d) is 70°C-90°C.
9. The process for making the fluorescent glue cake according to claim 1, characterized in that: The method of atomic layer deposition treatment in step (e) is as follows: The dried product is placed in an atomic layer deposition reaction chamber, which is evacuated to 10Pa under a nitrogen atmosphere, and the reaction chamber is heated to a reaction temperature of 50°C-90°C. Trimethylaluminum vapor is introduced as an aluminum source precursor for a time of 0.1s-10s, and the introduction is stopped. The reaction chamber is purged with nitrogen for a time of 1s-60s, and then ozone gas is introduced into the reaction chamber for a time of 0.1s-10s. The reaction chamber is purged with nitrogen again until a 1nm film layer is deposited, and the temperature is lowered to room temperature under a nitrogen atmosphere to obtain a coated product.
10. The process for making the fluorescent glue cake according to claim 1, characterized in that: The manufacturing process of the glass powder in step (e) is as follows: Mix B2O3, SiO2, ZnO and Na2O in a mass ratio of 10:60:20:10, calcine at 1000-1200℃ for 2h-4h, cool to room temperature, ball mill and pass through a 200-mesh sieve to obtain; In step (e), the mass ratio between the coated product and the glass powder is 1:(6-10); The temperature of the high temperature treatment in step (e) is 700° C.-800° C., and the time of the high temperature treatment is 10 min-30 min.
Citation Information
Patent Citations
Preparation method of Mn<4+> doped fluoride fluorescent powder material and method for surface modification of Mn<4+> doped fluoride fluorescent powder material
CN105038776A
Surface modification method of Mn<4+> doped fluoride red fluorescent powder material
CN107142102A
Red fluorescent glass ceramic and preparation method thereof
CN108249765A
Formula, preparation method and application of CsPbBr3: xDy < 3 + > quantum dot glass
CN113831022A
Garnet type fluorescent glass ceramic and preparation method thereof
CN114920463A